THE DEGREE OF ANTHROPOCENTRICITY OF TERMS RELATED TO EDUCATION AND UPBRINGING IN TERMINOGRAPHIC RESEARCH (American Journal of Interdisciplinary Research and Development, 2022)
Nowadays, as a result of the integration of such disciplines in world linguistics as pragmalinguistics, psycholinguistics, ethnolinguistics, discourse theory, the linguocultural direction of the anthropocentric paradigm is rapidly developing. The study of the factors, conditions and their nature that lead to the emergence of the category of education as a conceptual field in languages   of different systems, the specificity of the conceptual occurrence of the category of education, the study of interlinguistic phenomena as an object of study is one of the most pressing issues facing linguistics.